2017
DOI: 10.1364/ol.42.004179
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear pulse compression to 43  W GW-class few-cycle pulses at 2  μm wavelength

Abstract: High-average power laser sources delivering intense few-cycle pulses in wavelength regions beyond the near infrared are promising tools for driving the next generation of high-flux strong-field experiments. In this work, we report on nonlinear pulse compression to 34.4 μJ-, 2.1-cycle pulses with 1.4 GW peak power at a central wavelength of 1.82 μm and an average power of 43 W. This performance level was enabled by the combination of a high-repetition-rate ultrafast thulium-doped fiber laser system and a gas-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Based on our experimental results and on numerical modelling we have estimated the pulse peak power inside the fiber to ~5 GW. This value agrees well with the fact that we have observed ionization-induced spectral blueshifting at higher input pulse energies, which limits the peak power in the fiber similar to previous investigations [8].…”
Section: Experimental Setup and Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Based on our experimental results and on numerical modelling we have estimated the pulse peak power inside the fiber to ~5 GW. This value agrees well with the fact that we have observed ionization-induced spectral blueshifting at higher input pulse energies, which limits the peak power in the fiber similar to previous investigations [8].…”
Section: Experimental Setup and Resultssupporting
confidence: 93%
“…We are currently working on further optimization of the fiber core size, gas filling and dispersion control, which will lead to a significant increase in pulse peak power. In fact, we have recently demonstrated that selfcompression in ARHCFs is feasible at MHz-repetition rates [8], which means that more average power can be expected in the near future. These prospects make our approach a promising alternative to few-cycle pulse generation solely based on mid-IR parametric amplification [9], especially because it remains challenging to simultaneously achieve sub-two cycle, multi-GW pulses at high power in this case.…”
Section: Discussionmentioning
confidence: 99%
“…To date, it represents the strongest compression ratio in self-compression regime with a value of 17 that has been achieved using HCPCF technology. [114] 790 nm Self-compression 6.6 µJ 24 fs 6.8 fs~3.5 Krypton Hädrich et al [106] 1030 nm Postcompression 9 µJ 250 fs 30 fs~8.3 Krypton Guichard et al [115] 1030 nm Postcompression 70 µJ 330 fs 34 fs~9.7 Ambiant air Debord et al [31] 1030 nm Self-compression 450 µJ 600 fs 49 fs~12 Ambiant air Emaury et al [116] 1030 nm Postcompression 1.95 µJ 860 fs 48 fs~17.9 Xenon Balciunas et al [16] 1080 nm Self-compression 35 µJ 80 fs 4.5 fs~17 Xenon Wang et al [61] 1500 nm Self-compression 105 µJ 850 fs 300 fs~2.8 Ambiant air Gebhardt et al [117] 1820 nm Self-compression 41 µJ/34.4 µJ 110 fs 14 fs~7.8 Argon Murari et al [118] 2050 nm Postcompression 227 µJ 1.8 ps 285 fs~6.3 Argon…”
Section: Pulse Compressionmentioning
confidence: 99%
“…Actually, very strong amplification and broadband gain spectrum can be achieved with thulium-doped fibers. Highly developed fiber lasers, capable of generating several hundred micro joules [25,26] and more than tens of gigawatt peak power, have been achieved using external pulse compression [27]. However, millijoule energy level is still highly challenging for fiber lasers.…”
Section: Introductionmentioning
confidence: 99%